The 2015 Ming K Jeang Award for Excellence in Cell & Bioscience. Issue 1 (December 2016) - Shi, Yun-Bo
Abstract Two research groups led by Dr. Bin Gao of National Institute on Alcohol Abuse and Alcoholism, National Institutes of Health, MD, USA and Dr. Keji Zhao of National Heart, Lung, and Blood Institute, National Institutes of Health, MD, USA, respectively, won the 2015 Ming K Jeang Award for excellence inCell & Bioscience.